Bemerkenswerte Larvenvorkommen von Anax imperator (Leach) bei Sanit-Remy-de-Provence (Odonata: Anisoptera). - Heymer, Armin (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The author reports on a remarkable discovery of Anax imperator (Leach) larvae, which he found in an antique cistern in South France.